Finite element analysis of vehicle composite propeller shaft. (2022) - Singh, Utkarsh; Yadav, Pramod Kumar; Vidya, Shrikant; Srikanth, K.S.
Abstract: When designing a new automobile, weight reduction has become a common practice. In order to comply with stricter environmental regulations, it is necessary to reduce weight. If you'll pardon my technical jargon, manufacturers have been working hard to reduce the overall weight of their vehicles since the prototyping stage. A passenger car's propeller shaft was analyzed and optimized for weight reduction in this study. The shaft's natural frequency and durability were studied using finite element analysis and testing. Based on the structural analysis, it is found that propeller shaft weight reduced by 6.1%.